Ève K. Tremblay : vivre en soi - Crevier, Lyne (CV Photo)

(untitled) (Les Productions Ciel variable, 2000)
The photographer Ève K. Tremblay has created an allegorical work, reminiscent of "tales with a moral," in which nymphets and mature women swarm busily to embellish life. The places chosen close in on consenting victims, who ready themselves for any metamorphosis within a theatre steeped in romanticism—even fantasy. Tremblay's colour series L’Éducation sentimentale and Mimi et Jeanne dans le Hall of Fame show a rigour of composition that borders on the mannerism of good taste. Tremblay's portraits show an individual isolated in a landscape or in a set more or less in harmony with her state of mind.